Factors Influencing Tuberculosis Prevention Therapy (TPT) Drug Administration to Tuberculosis Patients' Home Contacts in the Working Area of the UPTD Health Center in Toapaya - Darmauli, Arta; Agusthia, Mira; M. Noer, Rachmawaty (Sahabat Publikasi Kuu, 2023)
Background : Tuberculosis is one of the 10 main causes of death Tuberculosis cases account for nearly half of the total number of tuberculosis cases in Indonesia. The phenomenon found at the UPTD Public Health Center in Toapaya was 10 people who were asked, 2 people knew about tuberculosis prevention therapy while 8 people did not know about tuberculosis prevention therapy. This study aims to determine the factors that influence the administration of TPT (Tuberculosis Prevention Therapy) drugs to tuberculosis patient household contacts in the Working Area of ​​the UPTD Health Center of Toapaya. The design of this research is descriptive quantitative with cross sectional approach. The sample in this study were all families who had contact at home with TB patients as many as 34 people and the data were analyzed using the chi square test. The results show that mild side effects from giving complete TPT were 55.9%, only 2.9% dropped out, good family support for giving complete TPT was 50.0%, only 11.8% dropped out, there was a significant difference, which (p -value 0.036 ≤0.05) this indicates that there is a difference in the proportion of giving TPT to respondents who experience good attitude and those who experience moderate attitude, p-value 0.025≤0.05 there is a difference in the proportion of giving TPT to respondents who experience good family support and those who experience adequate family support and a p-value of 0.000 ≤ 0.05 means that there is a difference in the proportion of respondents who experience mild side effects and those who experience severe side effects, Ha is accepted. In conclusion, there is a relationship between attitude, family support and side effects on administering TPT (Tuberculosis Prevention Therapy) drugs to tuberculosis patient household contacts in the Working Area of ​​the UPTD Health Center of Toapaya. Suggestions for nursing services do not only focus on pharmacological actions, but also for families, especially providing support for patient recovery